Decolonial Feminism and Racial Resistance: Ifemelu’s Writing in Americanah - Galvao, Naiana; Reis, Luciana da Silva (Em Tese, 2025)
This article offers a critical analysis of the trajectory of Ifemelu, the protagonist of Americanah, from the perspective of gender theory, aiming to highlight the practices of resistance present in her diasporic experiences. The theoretical framework is grounded in decolonial feminist studies, articulating the categories of race, class, and gender. The analysis of the corpus reveals that Ifemelu re-signifies structural oppressions through her critical writing in the blog Raceteenth, challenging conservative patterns within both social and academic spheres in the United States. The study concludes that the protagonist transforms patriarchal and racialized discourses into insurgent narratives, critically exposing the confrontation with structural sexism in contemporary societies.